Teachers’ Practices In Developing The 21st Century Skills Of Learners In The New Normal Education: Basis For Skills Enhancement Plan - John Paul C. Solon (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study assessed the strategies used by teachers in public elementary schools to develop learners’ 21st-century skills in the context of the new normal education and served as the basis for developing a skills enhancement plan for teachers. Using a descriptive research design, the study involved 134 public elementary school teachers from the Hermosa District, Schools Division of Bataan, selected through simple random sampling. Data were gathered using a self-administered survey questionnaire and examined utilizing descriptive and inferential statistical methods, such as the independent samples t-test, weighted mean, frequency counts, percentages, and analysis of variance (ANOVA). The findings showed that while communication skills were only occasionally worked on, teachers regularly used approaches that assist students’ information, media, and technology skills, learning and innovation skills, life and career skills, and soft skills. When teachers were grouped by age, years of service, and highest level of education, significant differences in their approaches emerged. However, no significant differences were observed when teachers were grouped by sex. Based on the findings, a skills enhancement plan was formulated to address areas least practiced and further strengthen teachers’ instructional practices. The study concluded that public elementary school teachers play a vital role in cultivating learners’ 21st-century skills despite the challenges posed by the new normal in education. Continuous professional development and the implementation of a responsive skills enhancement plan are recommended to further improve teachers’ practices and ensure the holistic development of learners.